Pemanfaatan Perkembangan Teknologi Informasi: Perdagangan Perempuan Dan Anak Untuk Eksploitasi Seksual Transnasional - Kosma Kaju Gae; Joko Sri Widodo; Edi Saputra Hasibuan (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study discusses the issue of trafficking of women and children for transnational sexual exploitation, focusing on the challenges faced in law enforcement and the use of technological developments as one of the modes in TPPO. Although the Indonesian government has taken several steps to address this issue, such as investigating and prosecuting cases of human trafficking, the results show a decline in investigations and convictions over the past few years. The development of information technology has been utilized by criminals to expand their networks and recruit victims boldly, which further worsens the situation. In addition, low levels of education and access to information among the community also contribute to the vulnerability of individuals to fraud and make them easy to fall into human trafficking networks. This study emphasizes the importance of improving education and access to information as a strategy to combat human trafficking